Legal Protection of Suspects’ Rights During the Investigation Stage Viewed from the Principle of Due Process of Law in the Indonesian Criminal Justice System - Fahrurazzi Fahrurazzi (International Journal of Law, Crime and Justice, 2026)
The protection of suspects’ rights during the investigation phase is a fundamental component of a fair and effective criminal justice system. This study examines the implementation of the principle of due process of law in Indonesia and its implications for safeguarding human rights in criminal investigations. Utilizing a normative legal research approach, supported by statutory and conceptual analysis, the research evaluates both the legal framework and practical application of suspects’ rights under the Indonesian Criminal Procedure Code (KUHAP), the 1945 Constitution, and international human rights instruments such as the ICCPR. Findings indicate that while Indonesia has established comprehensive regulations to protect suspects, the practical implementation remains inconsistent due to structural, cultural, and procedural challenges. Deviations such as limited access to legal counsel, incomplete documentation of interrogations, and occasional coercive practices undermine adherence to due process standards. The study highlights the critical need for regulatory improvements, capacity building for investigators, and strengthened supervision mechanisms to ensure full protection of suspects’ rights. Enhancing the conformity of investigative practices with due process principles is essential not only for safeguarding individual rights but also for maintaining public trust and the integrity of the Indonesian criminal justice system.